Character Merchandising and the Sporting Industry - Sadler, Pauline (2001)
This article examines issues related to the marketing strategy of "character merchandising", or the endorsement of products or services by famous people. The unauthorised use of a person's character may be prevented by the tort of passing off and an action under the Trade Practices Act 1974 (Cth). Cases discussed are Henderson v Radio Corp, Hogan v Koala Dundee Pty Ltd, Hogan v Pacific Dunlop Limited,Pacific Dunlop Limited v Hogan, Honey v Australian Airlines, Hutchence v South Sea Bubble Company, and Talmax Pty Ltd v Telstra Corp Ltd.